Uncommon presentation of sigmoid diverticulitis: colouterine fistula with pyometra - Solanki, Ashvi U.; Fakih, Kausar A.; Iyer, Sandhya; Singh, Mansha (International Journal of Research in Medical Sciences, 2024)
Pyometra is accumulation of pus in the uterine cavity. We present a case of a 76-year-old female presenting with pyometra secondary to a colouterine fistula in a case of sigmoid diverticulitis. Patient had come with complaints of pain in lower abdomen associated with loose stools and fever. Computed tomography (CT) of abdomen showed circumferential wall thickening of sigmoid colon with diverticulitis. 125 cc of fluid collection with air fluid level was seen in uterus abutting the sigmoid colon. On administering rectal contrast, leak of contrast was seen in the collection. In order to treat the sepsis, a diverting loop colostomy with dilatation of cervix and drainage of pyometra was done. Patient was planned for definitive surgery of sigmoid resection with hysterectomy after resolution of infection and inflammation. However, patient had a myocardial infarction in postoperative period and succumbed to the same. Since colouterine fistula secondary to diverticulitis is rare, we wish to add this case to current scientific literature.